2018
DOI: 10.1016/j.drugpo.2017.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Demand for and availability of specialist chemsex services in the UK: A cross-sectional survey of sexual health clinics

Abstract: Patients reporting chemsex regularly present to SHCs throughout the UK including rural areas. Given the potential negative health outcomes associated with chemsex, there is a need for local, high quality, appropriate services and training to minimise harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 5 publications
4
6
0
Order By: Relevance
“…Finally, the high engagement with SHCs among study respondents, particularly those reporting chemsex, has been seen elsewhere4 6 7 and is consistent with research demonstrating that chemsex-participating MSM are comfortable accessing SHCs14 and chemsex-related consultations in SHCs are common 8. However, we cannot know how much chemsex was addressed in the SHC visits reported by our study respondents.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Finally, the high engagement with SHCs among study respondents, particularly those reporting chemsex, has been seen elsewhere4 6 7 and is consistent with research demonstrating that chemsex-participating MSM are comfortable accessing SHCs14 and chemsex-related consultations in SHCs are common 8. However, we cannot know how much chemsex was addressed in the SHC visits reported by our study respondents.…”
Section: Discussionsupporting
confidence: 84%
“…The generally high SHC use presents a viable opportunity to provide chemsex-related sexual health services, particularly in venues providing HIV care. Considering findings from other research that only a third of SHCs have chemsex care-pathways in place,8 there have likely been missed opportunities to address wider health needs such as mental health and other drug-related harms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also showed this demand for specialist chemsex services and more efficient referral between sexual health clinics and drug treatment facilities [2,[36][37][38]. These findings are in accordance with findings from a quantitative study (n = 150) aimed at exploring the demand for, and availability of, chemsex services in the UK [52]. This online survey was distributed among sexual health clinic healthcare workers, and reported a need for chemsex training (99%) and a local chemsex specific service (81%).…”
Section: Discussionsupporting
confidence: 83%
“… 2 However, a survey of sexual healthcare providers across the United Kingdom found that people reporting chemsex regularly attend SHCs throughout the United Kingdom including rural areas. 24 What also remains unclear is whether SDU is taking place near the individuals’ home address or whether people are travelling for SDU but accessing care more locally. This study aimed to better measure and understand the similarities and differences in chemsex and sexualized drug use in MSM in urban and rural Britain.…”
Section: Introductionmentioning
confidence: 99%